Controlled Al3+ Incorporation in the ZnO Lattice at 188 °C by Soft Reactive Co-Sputtering for Transparent Conductive Oxides - Salvatore Sanzaro (Energies, 2016)
Transparent conductive oxide (TCO) layers, to be implemented in photo-anodes for dye-sensitized solar cells (DSCs), were prepared by co-deposition of ZnO and Al using pulsed-direct current (DC)-magnetron reactive sputtering processes. The films were deposited at low deposition temperatures (RT-188 °C) and at fixed working pressure (1.4 Pa) using soft power loading conditions to avoid intrinsic extra-heating. To compensate the layer stoichiometry, O2 was selectively injected close to the sample in a small percentage (Ar:O2 = 69 sccm:2 sccm). We expressly applied the deposition temperature as a controlling parameter to tune the incorporation of the Al3+ species in the targeted position inside the ZnO lattice. With this method, Aluminum-doped Zinc Oxide films (ZnO:Al) were grown following the typical wurtzite structure, as demonstrated by X-ray Diffraction analyses. A combination of micro-Raman, X-ray photoelectron spectroscopy (XPS) and spectroscopic ellipsometry (SE) analyses has shown that the incorporated host-atoms are Al3+ species in Zn2+ substitutional position; their amount increases following a direct monotonic trend with the deposition temperature. Correspondently, the c-axis strain into the layer decreases due to the progressive ordering of the lattice structure and reducing clustering phenomena. The maximum average Al content inside the film was ~2%, as measured by energy dispersive X-ray (EDX) spectroscopy, with a uniform distribution of the dopant species along the layer thickness traced by depth-profile XPS analyses. The optimised ZnO:Al layer, deposited at a rate of ~7 nm/min, exhibits high transmittance in the visible range (~85%) and low resistivity values (~13 mΩ × cm). The material therefore fulfils all the requirements to be candidate as TCO for low-cost DSCs on flexible substrates for large area technologies.